Ojibwe materials, Samuel George Morton Papers - Houghton, Douglass, 1809-1845; Wheaton, W.; Pitcher, Zina, 1797-1872; Schoolcraft, Henry Rowe, 1793-1864 (1835)
Letters discussing grave robbing of Indigenous ancestors' remains and observations of contemporary Native people. Houghton has been among Winnebago, Sacs, Foxes, and Sioux; can get Pottawatomi, Winnebago, and Chippewa skulls, but to get to know personages may take longer; Pitcher is sending sketch to go with a skull. Dr. Wheaton, evidently an army surgeon, spent 1822-1827 at Sault Ste. Marie, then at Mackinaw and Green Bay; consumption infrequent among soldiers, French residents, and Indians, which he attributes to the dry cold climate there; recommends such as treatment for sufferers. Pitcher resigned his Army job for private practice and to assist in forming the medical department of the new University of Michigan. He will send Chippewa skulls to help Morton "build up something like an American Golgotha." Schoolcraft advises Morton to come to Mackinac for treaty payments, where he can see Indians, and suggests a route he can take west to see more Indians. Mentions Chippewa, Menominee, Winnebagos, Stockbridge (Mohegan), Brothertowns, Oneidas, Sioux, Iowa, Sac and Fox Indians.